Functional dependency among elderly population in a rural area of Ernakulam district, Kerala, India - Devi, Indra; Sasidharan, Navami (International Journal Of Community Medicine And Public Health, 2023)
Background: Elderly populations with co-morbidities and sensory impairments are more likely to be functionally dependent on their activities of daily living. Objectives of the study were to determine functional dependency among the elderly population residing in a rural area of Ernakulam district, and also to determine the factors associated with functional dependency in the study population. Methods: A community-based cross-sectional study was conducted among 200 elderly people from rural area of Ernakulam district, Kerala. A non-probability convenient sampling method was used for the study participants. A semi-structured questionnaire was used to collect information about the socio-demographic questions, medical history and history of comorbidities. Barthel’s scale assessed activities of daily living and independent activities of daily living were assessed by Lawton’s scale. The statistical test was done using statistical package for the social sciences (SPSS) version 21 and a chi-square test of significance was used to find the association of various factors with functional dependency. Results: In Barthel’s scale using ADL score, fully dependent was found to be 2.5%. In the IADL score using Lawton’s scale fully dependent was found to be 0.5% among the study participants. Among the study participants, 57.9% of females and 42.1% of males have a visual impairment, 60% of females and 40% of males have a hearing impairment, 45.5% of females and 54.5% of males have a cognitive impairment. Conclusions: Comorbidities such as diabetes mellitus, cardiovascular diseases, osteoporosis, osteoarthritis, and cognitive impairment contribute to a decline in functional abilities among older adults.